2021
DOI: 10.3390/ijerph18094886
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention for Improving the Snacks and Beverages Brought to Youth Sports in the USA

Abstract: Objectives: The purpose of this study was to test a small-scale intervention and its ability to decrease total sugar intake and number of calories offered at youth sports games. Methods: This study was a pre/post-test quasi-experimental design. A flier was developed and distributed to parents. The flier aimed to decrease the sugar-sweetened beverages and increase the nutritional quality of food brought to games. Baseline data were collected in 2018 (n = 61). The flier was distributed prior to the start of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Therefore, the dietary guidelines have recommended limiting added sugar to 10% of total energy intake, yet national data indicates that about 80% of young children are exceeding this recommendation [ 39 ], with about 15 to 25% of total added sugars attributed to beverages, increasing to about 32% of added intake in adolescence [ 39 ]. Similarly, many studies have reported that children are exceeding recommendations for limiting added sugar, particularly due to the intake of sugary drinks [ 72 , 73 , 74 ]. In contrast, children in this study had few sugar-sweetened beverages, averaging less than one-half serving per day.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the dietary guidelines have recommended limiting added sugar to 10% of total energy intake, yet national data indicates that about 80% of young children are exceeding this recommendation [ 39 ], with about 15 to 25% of total added sugars attributed to beverages, increasing to about 32% of added intake in adolescence [ 39 ]. Similarly, many studies have reported that children are exceeding recommendations for limiting added sugar, particularly due to the intake of sugary drinks [ 72 , 73 , 74 ]. In contrast, children in this study had few sugar-sweetened beverages, averaging less than one-half serving per day.…”
Section: Discussionmentioning
confidence: 99%